Pendampingan teknologi hidroponik fodder di Gampong Cot Karieng Kecamatan Blang Bintang, Aceh Besar (Fodder hydroponic technology assistance in Cot Karieng Village Blang Bintang Sub-District, Aceh Besar) - Azhari, A; Syakur, S; Ferasyi, Teuku Reza; Rastina, R; Nurliana, N; Ismail, I; Novita, Andi (Buletin Pengabdian, 2023)
The livestock fattening business carried out by the partner group in Cot Karieng Village Blang Bintang Sub-District, Aceh Besar is a part-time business with a traditional pattern. Provision of feed only relies on efforts to find field grass every day. Meanwhile, the availability of forage is very fluctuating wherein during the rainy season, fresh forage is abundantly available, while during the dry season, it is very scarce. The purpose of this activity was to increase the knowledge and skills of partner groups in procuring animal feed, especially for the dry season. The solution offered was the use of hydroponic forage cultivation technology (hydroponic fodder). The seed of the fodder plant used was corn seed. The program implementation method was carried out through a participatory approach (partners were involved and worked together) starting from the initial stage to the final stage. In the first stage, coordination meetings were held so that all involved parties understood the scope of activities. In the second stage, training was carried out on hydroponic fodder cultivation methods, while assembling and applying technology which included making fodder houses (green-houses), installing green-house water networks and the process of cultivating hydroponic fodder plants was conducted in in the third stage. The stages of the cultivation process included washing and disinfecting the corn seeds by immersing them in a 1% chlorine solution for 15 minutes, then the seeds were spread out on trays. Seed moisture was always maintained by an aeroponic system every 1-2 hours for 10 minutes. After 14 days of cultivation, 1 kg of corn seed produced 6 kg of corn fodder. After washing and air-drying the corn fodder was ready to be given to livestock. The results achieved from all the implementation of this activity are the availability of facilities for the production of fodder hydroponic fodder system and the partner groups already have the skills of cultivating fodder using hydroponic fodder system.